TALENT MANAGEMENT CHALLENGES IN A PANDEMIC COVID-19: A LITERATURE REVIEW - Raden Isma Anggraini; Mohammad Syamsul Ma’arif (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Covid-19 pandemic shows the unpreparedness of most business sectors in responding and managing an unprecedented organization (Hartono, 2020). In the process, talent management is considered of paramount importance as many organizations struggle to implement effective talent management practices to survive. This study aims to answer questions about what challenges business organizations to face in implementing talent management during the Covid-19 pandemic. We used a systematic literature review to synthesize findings qualitatively. The secondary data were collected for this study. This study found that the challenges faced by business organizations in implementing talent management during the Covid-19 pandemic, namely: the transformation of skills that will affect technology, changes in the mindset of work from the office, readiness and agility in the face of rapid change, the increasing importance of technology and intelligence and business organizations are required to embrace diversity. Organizational resilience can provide value to a changing world through ecological, economic, and social development. Creative talent management can also be applied to assist organizations in maintaining their business continuity and providing a competitive advantage in this rapidly changing pandemic environment.